PENGGUNAAN PENDEKATAN KUIS TIM UNTUK MENINGKATKAN TANGGUNG JAWAB INDIVIDU DALAM KELOMPOK BELAJAR GEOGRAFI SISWA KELAS X-8 SMA NEGERI 1 DURENAN TRENGGALEK - Murdani, Murdani (Universitas Nusantara PGRI Kediri, 2015)
ABSTRACT: Self develovment trough active learning by using Quiz Team Approach is centered on thestudent’s variety during the activities in turning the dinamic of the student group in learning. It begins fromunderstanding the concept of learning material, making questions to design group activity, deviding the groupwork every, planning the presentation until giving such kind of achievement in the form of score and crownedthe best group for every session. This research is aimed to increase individual responbility in finishing theassigment in a group, dua two self development process.The subject of this research is the students of X-8, 2014/2015 Academic Year. This classroom actionresearch is designed into 2 cycles. Wich every cycle consist of many steps: planning, doing the research,observation, reflexion. The result of action in one cycle is in the form of the student’s active, the developmentof self aspect self improvement from the students, is evaluated as the material to design the next action for thenext cycle. The material used as the object of the research is Quiz Team Active Learning model and theimplementation.The research result showed that the applied of active learning model by using Quiz Team Approachbe able to increase individual responsibilty in a group study. This learning model, the researcher meant byusing Quiz Team Approach, got positive response from students by the indicator from the result of “angket”analysis at the end of activity and the increasing of finishing the assignment and “unjuk kerja”. The student’sachievement is also become raising in 1st cycle the average score of formative 72,50 and the “ketuntasan” ofthe learning result is 78,57%, meanwhile at the 2nd cycle, its become increasing on the average of formativescore 80,35 and 90,47%.Key Words: Quis team learning model, individual responsibility, group studyPENDAHULUANaspek dan nilai-nilai tanggungjawab siswa terhadap